Explore a diverse range of topics and get answers from knowledgeable individuals on IDNLearn.com. Our platform is designed to provide quick and accurate answers to any questions you may have.
Sagot :
Answer:
=
−
7
3
=
−
7
Step-by-step explanation:
=
−
±
2
−
4
√
2
x={b}}^{2}-4{a}}{2{a}}}
x=2a−b±b2−4ac
Once in standard form, identify a, b, and c from the original equation and plug them into the quadratic formula.
3
2
+
2
8
+
4
9
=
0
3x^{2}+28x+49=0
3x2+28x+49=0
=
3
a={3}}
a=3
=
2
8
b={28}}
b=28
=
4
9
c={129}{49}}
c=49
=
−
2
8
±
2
8
2
−
4
⋅
3
⋅
4
9
√
2
⋅
3
=
−
2
8
±
1
4 over
6
=
−
2
8
+
1
4
6
x={-28+14}{6}
x=6−28+14
=
−
2
8
−
1
4
=
−
7
3
x=-{7}{3}
x=−37
=
−
7
=
−
7
3
=
−
7
We are happy to have you as part of our community. Keep asking, answering, and sharing your insights. Together, we can create a valuable knowledge resource. Thank you for choosing IDNLearn.com. We’re here to provide reliable answers, so please visit us again for more solutions.